CLASSROOM ACTION RESEARCH THROUGH THE CREATION OF THE "BABAD ALAS KALUMPRING" DANCE AT SMP NEGERI 59 SURABAYA - Nuriyanto, Fani Dwi; Wijaya, Rosy Prischila; Yudha, Septian Brahmatya; Dewi, Shinta Krisiana; Tyapuspita, Sisnanda; Patria, Asidigisianti Surya; Arif, Andy Rahman (Acintya, 2025)
This class action research aims to determine the improvement of the learning outcomes of Cultural Arts students in grade VII of SMP Negeri 59 Surabaya through the creation of a literary work entitled "Babad Alas Kalumpring". This research is motivated by the low involvement and learning outcomes of students in art learning, especially performing arts. Cultural Arts as a subject in junior high school has an important role in shaping creative, appreciative, and expressive characters in students. However, the reality at SMP Negeri 59 Surabaya shows that the learning outcomes of Cultural Arts are still low, especially in the aspect of appreciation and creation of performing arts. Many students lack a holistic understanding of the concept of performing arts and tend to be passive in the learning process. The method used in this study is the Kemmis and McTaggart model class action research which consists of planning, action, observation, and reflection in two cycles. Data was collected through observation, tests, documentation, and interviews. The results of the study showed a significant increase in material understanding, active participation, and students' skills in creating and displaying artworks. In conclusion, the creation of sendratari based on local stories can be an effective strategy to improve the learning outcomes of Cultural Arts. This study shows that the creation of the "Babad Alas Kalumpring" dance is effective in improving the learning outcomes of Cultural Arts at SMP Negeri 59 Surabaya. Through this project-based creative approach, grade VII A students become more active, creative, and able to work together optimally. The drama creation project encourages an increase in student participation from 70% in Cycle I to 90% in Cycle II, as well as increasing the completeness of cognitive learning outcomes from 68% to 87% of students who achieve grades above KKM.